Fenologia remota próxima e atributos foliares de vegetações sazonais - Ramos, Desirée Marques (Universidade Estadual Paulista (Unesp), 2021)
Drivers of leafing phenology are still unknown for several tropical system holding most of the global diversity of species. Remote sensing estimates leafing time over continental (satellite) and regional/local scales (digital cameras - near-surface phenology) by applying several greenness indices. Near-surface remote phenology using digital cameras enhances the temporal resolution of phenological information at individual tree, species, and community scale. The present project proposes to investigate, based on near-surface phenology, the proximate drivers of seasonal tropical plant phenology, i.e., which climatic factors are responsible for changes in leaf phenophases in two ecosystems: cerrado and caatinga. How climate affect the timing of leafing season in communities varying in their degree of seasonality and in time and length of growing (leafing) season? How is the timing of growth linked to plant physiology (i.e., which plant traits change first, e.g., water contents prior to mineral contents during leafing or before flowering)? Determine major plant phenology strategies based on leafing timing and leaf traits. How many functional groups are detected in the caatinga compared to cerrado?
Near-remote henology and leaf traits of seasonal vegetations
Keywords: Caatinga; Seasonally dry tropical forest; Leafing patterns; Floresta tropical sazonalmente seca; Padrões de folhagem